Assisted Dying: An International Overview. Issue 2 (26th March 2015) - Badham, Paul
Abstract : Legalising assisted dying is a response to increasing human longevity and that much of this is taken up by terminal illness. Assisted dying and voluntary euthanasia are legal in a growing number of jurisdictions across the world. Opposition to this in England and Wales is largely fuelled by fears over its possible consequences for health care. However, examination of the history of assisted dying and the quality of health care in those jurisdictions which permit it shows that such fears lack evidential support. The Euro Health Consumer Index is drawn on to illustrate this. 1